Efficient acyloxymethylation of psilocin and other tryptamines yielding ACOM prodrugs for psychedelic-assisted therapy - Stirn, Judith; Klein, Christian D. (Archiv der Pharmazie, 2025)
Acyloxymethyl (ACOM) derivatives of tryptamines such as the psychedelic drug psilocin and the anti-migraine drug sumatriptan bear potential as prodrugs. Previous synthetic approaches suffer from insufficient chemoselectivity between the desired functionalization of the phenolic (psilocin) or sulfonamide (sumatriptan) groups versus other reactive groups in the parent drugs. We report a novel synthetic route toward ACOM prodrugs of tryptamines via the chemoselective installation of a carbamate protecting group at the indole nitrogen by means of a Heller-Sarpong reagent and final deprotection under extremely mild conditions. This enables delicate transformations such as the O-acyloxymethylation of psilocin or the N2-acyloxymethylation of sumatriptan. Several novel O-ACOM ethers of hydroxytryptamines were obtained and evaluated in vitro for their potential as novel prodrugs for psychedelic therapy. The rate of bioactivation in human plasma may be adjusted to rapid (t1/2 < 1 min) or slow (t1/2 > 240 min) kinetics by varying the acyl residue in the ACOM promoiety. Irrespective of the acyl residue, short half-lives in human saliva will likely preclude the sublingual or buccal application of ACOM ether prodrugs of hydroxytryptamines, while other routes such as peroral, transdermal, nasal, or intravenous administration may be pursued.
Gesehen am 24.11.2025